A study on the heat treatments of deformed AA5083 by the ECAE process. (5th May 2009) - Huarte, B.; Luis, C.J.; Luri, R.; Leon, J.
The process Equal Channel Angular Extrusion (ECAE) is an innovate technique that allows us to obtain submicrometer and even nanometre grain size in the processed materials without a noticeable modification in the cross section. Ultra fine-grained materials are currently of great scientific interest due to their unusual mechanical properties, such as high tensile strength, ductility and the possibility of getting superplasticity at low temperatures. The billet deformed by ECAE retains the same cross-sectional area, so it is possible to repeat the process in several cycles. Therefore, very high plastic strains can be accumulated in the billet. This work presents a study on the recrystallation temperature of the AA50803 processed by ECAE. The different annealings were carried out after processing the AA5083 up to N = 4 at room temperature. The main aim of this work is to achieve a recrystallised and homogeneous microstructure after the deformation imparted by ECAE process, because after the ECAE passages there exists a non-uniform and high degree of dislocation in the material. Optical microscopy and scanning electronic microscopy were used in order to determine the microstructure of the material.